Hubungan Makna Antarklausa Dalam Kalimat Majemuk Bertingkat Pada Terjemahan Surah Albaqarah - YULIYATI, HERLINA EKA; , Prof. Dr. Markamah. M.Hum (2016)
The problems that the lift in this study is about the relationship of meaning in sentences compound antarklausa storied Al-Baqara translation. Sentences contained in Al-Baqara contain different types of relationships of meaning and assorted clauses. Relationship meanings and clause in the translation of Al-Baqara. This study aims to (1) explain how to form relationships within the meaning antarklausa storey complex sentences in translations Al-Baqara (2) describe the suitability of the use of conjunctions contained in Al-Baqara translation with conjunctions used. This study uses the methods and techniques used agih that vanished techniques, strategies used in this penenlitian is a qualitative approach. From one data source (Al-Qur'an) which is used in this research that has found as many as 5 form a successful relationship in the analysis of meaning in accordance with the provisions. 23 meaning a causal relationship, meaning 3 causal relationship conjunctions so, three relationships of meaning causation, meaning the relationship 5 goals, 3 meaning relations order. Data were each menjukan relationships and their meaning conjunctions appropriate and not appropriate. Use of appropriate conjunctions, the conjunctions, conjunctions so, conjunctions if, conjunctions because it, conjunctions so or so. And conjunctions are not suitable among other conjunctions then that is not appropriate based on the content of Al-Baqara translation.